Implementing maqasid sharia: Impact on stability of Indonesian Islamic banks - Analia, Adinda Lia; Hakim, Abdul; Anto, Mohammad Bekti Hendrie; Perdana, Andika Ridha Ayu (Faculty of Economics, Universitas Islam Indonesia, 2024)
Purpose – This study analyzes the relationship between maqasid sharia and the stability of Islamic banks in Indonesia.Methodology – This study uses annual balanced panel data of eight Islamic banks in Indonesia from to 2010-2020 and utilizes a random effects model (REM) approach with the generalized least squares (GLS) method. The dependent variable is the Z-score as a proxy for bank stability, and the independent variables are bank size, the maqasid index (MI), capital adequacy ratio (CAR), gross domestic product (GDP), inflation, and interest rate.Findings – This research reveals that the stability of Islamic banking in Indonesia decreased over the study period, whereas maqasid performance increased. Furthermore, this study shows that the maqasid index and GDP negatively influence the Z-score, while bank size and CAR have a positive influence. We found no influence of inflation or the interest rate on the Z-score. The negative impact of the Maqasid index denotes poor management and financing quality, which is linked to the slanted achievement of the three Maqasid objectives (education, justice, and maslahah) during the study period.Implications – Policymakers, industry, and academics can use the research findings as recommendations to strengthen the stability of Islamic banks and their role in promoting welfare.Originality – This study employs the maqasid index as a proxy for Islamic bank performance to analyze its influence on bank stability.